Factors that Influence Customer's Intentions to Revisit Cafe: Case Study of Siete Cafe in Bandung - Cibro, Yenny Erica Br.; Hudrasyah, Herry (Journal of Business and Management, 2017)
AbstractSiete Café is one of popular café in Bandung located at Jl. Sumur Bandung No.20. Siete Café was established on November 11th, 2011 by 6 students of Bandung Institute of Technology. The target market of Siete Café is college students from universities and employees in Bandung. In running the business and apply the marketing strategy, Siete Café implementing 7P’s marketing mix (Products, People and Process, Price, Place, Promotion, and Physical Evidence) in order to improve customer satisfaction that will influence customer’s decision to revisit in Siete Cafe. But in 2015, Siete Café had decreased of total sales numbers caused by the decreased of visitor numbers in that period. This research aims to identify and analyze the relationship between the factors of Siete Cafe’s marketing mix (food quality, service quality, place, price, promotion, physical evidence) as an independent variables to customer satisfaction as the dependent variable, and also the relationship between customer satisfaction as independent variable toward revisit intentions as a dependent variable. The data were gathered using questionnaire and distributed to 184 customers who had visited Siete Cafe. The result showed that the factor of quality food, place, price and promotion does not have a significant effect (sig> 0.05) towards customer satisfaction in Siete Cafe. While the quality of service and physical evidence has a significant impact on customer satisfaction in Siete Cafe value (sig> 0.05 and beta = 0.281; 0.309). The results also found that the squared R-value of this study marks a 0.298 value or 29.8%, which signifying the effect of Food Quality, Service Quality, Place, Price, Promotion, and Physical Evidence of overall Customer Satisfaction. The number is also telling the existence of a 70.2% contribution of the Customer Satisfaction Measurement that is not covered in this study. However, the value of the squared R is 0.503, or 50.3% of the effect of Customer Satisfaction toward the Revisit Intention to Siete Cafe. The result will be functional for Siete Cafe’s management to evaluate and enhance the factors that might enhance the customer satisfaction to induce their intention to revisit, specifically physical evidence and service quality. Siete Cafe also needs to analyze the market trend in order to improve marketing strategies. Keywords: Cafe, Marketing mix, Customer satisfaction, Revisit intention